Targeting Labour Market Programmes - Results from a Randomized Experiment - Stefanie Behncke; Markus Frölich; Michael Lechner (Swiss Journal of Economics and Statistics, 2009)
We evaluate a randomized experiment of a statistical support system developed to assist caseworkers in Swiss employment offices in choosing appropriate active labour market programmes for their unemployed clients. The support system was piloted in several employment offices in which, randomly, half of the caseworkers used the system and the other half acted as control group. Caseworkers retained full discretion about the choice of active labour market programmes, and the evaluation results showed that caseworkers largely did not follow the statistical support system. This indicates that stronger incentives are needed for caseworkers to comply with statistical profiling and targeting systems.
Keywords: J68; 330; Profiling; active labour market programmes; ALMP; statistical treatment rules; unemployment; public employment services